Postneonatal under-5 mortality in peri-urban and rural Eastern Uganda, 2005–2015 - Peter Waiswa; Claudia Hanson; Atsumi Hirose; Tobias Alfvén; Dan Kajungu; Valerie Tusubira (BMJ Global Health, 2020)
Introduction Community and individual sociodemographic characteristics play an important role in child survival. However, a question remains how urbanisation and demographic changes in sub-Saharan Africa affect community-level determinants for child survival.Methods Longitudinal data from the Iganga/Mayuge Health and Demographic Surveillance Site was used to obtain postneonatal under-5 mortality rates between March 2005 and February 2015 in periurban and rural areas separately. Multilevel survival analysis models were used to identify factors associated with mortality.Results There were 43 043 postneonatal under-5 children contributing to 116 385 person years of observation, among whom 1737 died. Average annual crude mortality incidence rate (IR) differed significantly between periurban and rural areas (9.0 (8.1 to 10.0) per 1000 person-years vs 18.1 (17.1 to 19.0), respectively). In periurban areas, there was evidence for decreasing mortality from IR=11.3 (7.7 to 16.6) in 2006 to IR=4.5 (3.0 to 6.9) in 2015. The mortality fluctuated with no evidence for reduction in rural areas (IR=19.0 (15.8 to 22.8) in 2006; IR=15.5 (13.0 to 18.6) in 2015). BCG vaccination was associated with reduced mortality in periurban and rural areas (adjusted rate ratio (aRR)=0.45; 95% CI 0.30 to 0.67 and aRR=0.56; 95% CI 0.41 to 0.76, respectively). Maternal education level within the community was associated with reduced mortality in both periurban and rural sites (aRR=0.83; 95% CI 0.70 to 0.99; aRR=0.90; 95% CI 0.81 to 0.99). The proportion of households in the poorest quintile within the community was associated with mortality in rural areas only (aRR=1.08; 95% CI 1.00 to 1.18). In rural areas, a large disparity existed between the least poor and the poorest (aRR=0.50; 95% CI 0.27 to 0.92).Conclusion We found evidence for a mortality decline in peri-urban but not rural areas. Investments in the known key health (eg, vaccination) and socio-economic interventions (education, and economic development) continue to be crucial for mortality declines. Focused strategies to eliminate the disparity between wealth quintiles are also warranted. There may be equitable access to health services in peri-urban areas but improved metrics of socioeconomic position suitable for peri-urban residents may be needed.